2014
DOI: 10.1523/jneurosci.1491-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Incentive Framing on Performance Decrements for Large Monetary Outcomes: Behavioral and Neural Mechanisms

Abstract: There is a nuanced interplay between the provision of monetary incentives and behavioral performance. Individuals' performance typically increases with increasing incentives only up to a point, after which larger incentives may result in decreases in performance, a phenomenon known as "choking." We investigated the influence of incentive framing on choking effects in humans: in one condition, participants performed a skilled motor task to obtain potential monetary gains; in another, participants performed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 37 publications
(19 reference statements)
3
52
0
Order By: Relevance
“…This evidence concurs with recent expected value accounts of cognitive control (Botvinick & Braver, 2015;Kool, Gershman, & Cushman, 2017;Kurzban, Duckworth, Kable, & Myers, 2013;Shenhav et al, 2017), which propose that the degree (and intensity) of engagement in an upcoming cognitive computation is based on a cost-benefit analysis. In line with this account, it has been shown repeatedly that enhancing motivation, for example by offering reward, affects performance on cognitive control paradigms (Aarts, van Holstein, & Cools, 2011;Botvinick & Braver, 2015;Chib, Shimojo, & O'Doherty, 2014;Chib, De Martino, Shimojo, & O'Doherty, 2012;Manohar et al, 2015;Padmala & Pessoa, 2011). Increasing the value or benefit of a demanding computation, such as task switching, seems to outweigh perceived demand costs.…”
Section: Catecholaminergic Modulation Of Learning and Choice About Comentioning
confidence: 84%
“…This evidence concurs with recent expected value accounts of cognitive control (Botvinick & Braver, 2015;Kool, Gershman, & Cushman, 2017;Kurzban, Duckworth, Kable, & Myers, 2013;Shenhav et al, 2017), which propose that the degree (and intensity) of engagement in an upcoming cognitive computation is based on a cost-benefit analysis. In line with this account, it has been shown repeatedly that enhancing motivation, for example by offering reward, affects performance on cognitive control paradigms (Aarts, van Holstein, & Cools, 2011;Botvinick & Braver, 2015;Chib, Shimojo, & O'Doherty, 2014;Chib, De Martino, Shimojo, & O'Doherty, 2012;Manohar et al, 2015;Padmala & Pessoa, 2011). Increasing the value or benefit of a demanding computation, such as task switching, seems to outweigh perceived demand costs.…”
Section: Catecholaminergic Modulation Of Learning and Choice About Comentioning
confidence: 84%
“…Furthermore, under certain circumstances, increased incentives can paradoxically result in less-efficacious instrumental performance, an effect known as choking that has been linked to dopaminergic regions of the midbrain (Chib et al 2014, Mobbs et al 2009, Zedelius et al 2011). For example, Ariely et al (2009) offered participants in rural India the prospect of winning large monetary amounts relative to their average monthly salaries.…”
Section: Interaction Among Behavioral Control Systemsmentioning
confidence: 99%
“…One theory is that choking effects reflect a maladaptive return of behavioral control to the goal-directed system in the face of large potential incentives in a situation in which the habitual system is better placed to reliably execute a skilled behavior. Although some results support this hypothesis (Lee & Grafton 2015), others support an alternative account whereby Pavlovian effects elicited by cues could engage Pavlovian skeletomotor behaviors, such as appetitive approach or aversive withdrawal, that interfere with the performance of the habitual skilled motor behavior (Chib et al 2012, 2014). More than one of these ideas could hold true, as behavioral choking effects may have multiple causes arising from maladaptive interactions between these systems.…”
Section: Interaction Among Behavioral Control Systemsmentioning
confidence: 99%
“…An interesting possibility is that the beta modulations stemmed from interactions between these sensorimotor regions and the basal ganglia (Jenkinson and Brown, 2011), which are believed to influence movement vigor through motivation-related dopamine signals that dictate the worth of voluntary actions (Shadmehr and Krakauer, 2008;Turner and Desmurget, 2010;Berke, 2018). For instance, it has been shown that activity in the ventral striatum, which receives dopaminergic inputs from the substantia nigra pars compacta and ventral tegmental area (Tritsch et al, 2012), predicts incentive-driven changes in motor performance (Chib et al, 2012(Chib et al, , 2014 and vigor (Opris et al, 2011). Hence, the positive correlation between pre-movement beta activity and MTs in the present study strongly, though indirectly, suggests a link between beta activity and nigrostriatal activity.…”
Section: Discussionmentioning
confidence: 99%